EFEKTIFITAS PERENDAMAN TELUR DALAM LARUTAN HORMON TIROKSIN DENGAN DOSIS BERBEDA TERHADAP DAYA TETAS, PERTUMBUHAN DAN KELANGSUNGAN HIDUP LARVA IKAN NILEM (Osteochilus hasseltii) - Taufik Budhi Pramono; Yola Vebiola; Sri Marnani; Marhaendro Santoso; Kasprijo . (UNIVERSITAS MUHAMMADIYAH PONTIANAK, 2021)
High mortality in the larvae stage was a major problem in fish hatchery efforts. Efforts that can be done through the hormonal stimulation with the utilization of thyroxine hormone. The purposes of this research was to determine the effect of immersing eggs in a solvent of thyroxine hormone at different doses on hatchability, growth and survival nilem fish larvae (Osteochilus hasseltii). The research method use a complete randomized design (RAL). Treatments in this research were A (control), B (0.05 mg / L), C (0.10 mg / L), D (0.15 mg / L). The research variables observed were hatchery, an absolute long-term growth, relative long-term growth and the survival. The results of this research showed that the soaking of eggs in thyroxine hormone at different doses had no significant effected on hatchability (P> 0.05) but had a significant effected on growth, and survival of nilem fish larvae (P